The novel pretreatment immune prognostic index discriminates survival outcomes in locally advanced non-operative esophageal squamous cell carcinoma patients treated with definitive chemoradiotherapy: a 6-year retrospective study - Yilin Yu; Haishan Wu; Jianjian Qiu; Dongmei Ke; Yahua Wu; Mingqiang Lin; Qunhao Zheng; Hongying Zheng; Zhiping Wang; Hui Li; Lingyun Liu; Jiancheng Li; et al. (Translational Oncology, 2022)
Objective: We aimed to construct risk stratification to help set individualized treatment strategies and intensities for different subgroups of patients. Methods: The Esophagus Immune Prognostic Index (EIPI) scores were constructed according to the levels of derived neutrophil-to-lymphocyte ratio (dNLR) and lactate dehydrogenase (LDH) before treatment, and the patients were divided into low-, medium-, and high-risk groups. Finally, restricted cubic splines (RCS) were used to explore the relationship between dNLR, LDH, and survival outcomes. Results: The median follow-up period of overall survival (OS) and progression-free survival (PFS) were 25.2 and 17.6 months, respectively. Multivariate Cox regression analysis showed dNLR were the independent prognostic factors that were associated with OS and PFS. The 3-year OS and PFS rates in the low-, medium-, and high-risk groups were 44.4% and 38.2%, 26.1% and 23.6%, and 10.5% and 5.3%, respectively. Patients who received chemotherapy had better OS and PFS than those who did not receive chemotherapy in low-risk and medium/high-risk groups (all p < 0.05). Besides, the results also revealed significant differences for patients with clinical T, N, and TNM stage groups of the OS and PFS in different risk groups. Finally, RCS analysis indicated a nonlinear relationship between the dNLR, LDH, and survival for esophageal squamous cell carcinoma (ESCC) patients. The death hazard ratios of dNLR and LDH sharply increased at 1.97 and 191, respectively. Conclusions: In summary, the EIPI, a novel inflammatory-based and immune-related prognostic score, is an independent prognostic indicator in locally advanced ESCC patients undergoing definitive chemoradiotherapy (dCRT).